Feasibility Analysis of Djoglo Restaurant Business in Lampung Regency South Area Reviewed from the Aspects of Market, Marketing, And Sharia Financing - Atridayansyah, Reza; Fatih Fuadi; Dimas Pratomo (International Journal of Economics (IJEC), 2025)
This study aims to analyze the feasibility of the Djoglo Restaurant business in South Lampung Regency from the market, marketing, and sharia financing aspects to support strategic decision making for the development of traditional culinary businesses. The study uses a qualitative approach with a case study method that was carried out for three months, with primary data obtained through in-depth interviews with owners, managers, employees, consumers, and direct observation, as well as secondary data from financial reports and internal company documents analyzed using an interactive analysis model with triangulation to ensure data validity. The results of the study indicate that the Djoglo Restaurant is very feasible to be developed from the three aspects studied, with the market aspect showing very good potential through an average of 180-220 people visiting per day, clear segmentation with a family dominance of 45%, and consumer satisfaction reaching 92% for the atmosphere of the place; the marketing aspect shows high effectiveness with sales growth of 20% per year and customer retention of 72% through an integrated marketing mix; and the sharia financing aspect shows that the musyarakah scheme with a ratio of 60:40 is the most suitable for an expansion of Rp 800 million with very positive feasibility indicators including NPV of Rp 1.24 billion, IRR of 42%, and a payback period of 2.3 years. This study provides practical contributions in the form of strategic recommendations for management in business expansion using sharia financing and optimizing marketing strategies, while enriching the literature on the feasibility of traditional culinary businesses with a sharia financing approach which is still limited in Indonesia, especially in the context of restaurants in the regions.